Chameleon Coping Behavior In Frances Parkinson Keyes'Steamboat Gothic : An Individual Psychological Approach - Kristianti, Rizky (2005)
The problem of this study is how chameleon coping behavior is reflected in Frances Parkinson Keyes' Steamboat Gothic. The study is focusing on the chameleon coping behavior that is done by the main character of this novel, Clyde Batchelor. The study aims at the way chameleon coping behavior occurs in the life of Clyde Batchelor and its effects on his surrounding. This research is using the text of novel as the primary data and the materials about psychological approach in chameleon coping behavior and the author's bibliography as the secondary data. The analysis is using descriptive analysis to describe what is meant by chameleon coping behavior, and content analysis to dissect the work into its smaller element particularly to highlight the psychological conflict of chameleon coping behavior. The Individual Psychological approach of Alfred Adler is used to reconstruct the major character's behavior in chameleon coping behavior. Based on analysis on previous chapters, the writer has come to a conclusion that in this novel, Steamboat Gothic, Frances Parkinson Keyes portrayed a portrait of psychological phenomena, which is a chameleon coping behavior in the main character. Chameleon coping behavior is a psychological way of escaping from enemies by doing an act like a chameleon, which is the change of self-condition into the same condition of the surrounding that makes him invisible. The change includes the change of identity, the change of look and appearance, the change of social behavior, and the change of personality. In this novel, Frances Parkinson Keyes implied her view in the theme of this novel, which is "a man writes and decides his own destiny". This theme is related with the psychological phenomena of chameleon coping behavior, reflected in the actions of the main character by hiding his real identity, changing his look and appearance, and changing his behavior. Chameleon coping behavior is done as a way of a man to write and decide his own destiny. The man writes and decides what he wanted to be, what he wanted to look like, and what he wanted his society to see him like. The coping behavior is done in order to make himself invisible from his enemies, therefore he can avoid the danger he fears most.